Analysis of Propaganda in the Russia-Ukraine Conflict on YouTube Tribun Timur (March-July 2024) - Achlis, Muhammad Nur; Permatasari, Diah Ayu; Purwanto, Hari; Rezasyah, Teuku; Supriyadi, Asep Adang (Journal of Law, Politic and Humanities, 2025)
This study, titled Analysis Propaganda in the Russia-Ukraine Conflict on YouTube Tribun Timur (March-July 2024), aims to reveal propaganda patterns in digital news coverage of the Russian-Ukrainian conflict. The research subjects are five videos with the highest engagement on the Tribun Timur YouTube channel from March to July 2024. This study uses content analysis and literature review methods to identify the forms of messages, symbols, and visual communication techniques used in shaping public opinion. The results of the study show that the videos consistently portray the military superiority of Russia and undermine the position of Ukraine using specific propaganda techniques such as the use of negative terminology, symbolic visuals, the omission of opposing information, and dramatic narratives. In addition, a narrative pattern was found that aligns with Russia's “firehose of falsehood” propaganda model, which is massive, fast, and inconsistent with objective truth. The conclusion of this study states that YouTube Tribun Timur has become a potential channel for the spread of transnational propaganda that could threaten Indonesia's information resilience if not subject to continuous monitoring and critical analysis by the relevant authorities.